Sayyidina Ali And Khawarij’s Story in Qawaid Al-Iman fi Bayan Al-Iman Manuscript by Sheikh Tengku H. Muhammad bin Alim - Zahara, Mina; Fahri, Ismail; Marselia, Febi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study explores two primary themes: the Qawaid al-Iman fi Bayan al-Iman manuscript by Sheikh Tengku H. Muhammad bin Alim, and the narrative of Sayyidina Ali's interrogation by the Khawarij, as presented in this manuscript. Employing a qualitative research methodology, the study aims to examine these issues in depth, utilizing a philological approach to analyze the text. The research adopts a descriptive framework to detail the manuscript's characteristics, with an emphasis on the systematic steps of philological analysis, including text identification, manuscript cataloging, description, comparative study, transliteration, and translation. The findings indicate that the manuscript titled Qawaid al-Imani fi Bayan al-Iman (The Principles of Faith: An Exposition of the Pillars of Belief) was authored by Sheikh Tengku H. Muhammad bin Alim during his Islamic missionary work in Muara Jernih Village between 1970 and 1980, with the work completed five years prior to his death. The manuscript spans 127 pages and is written in Malay Arabic. In addition, the study explores the episode in which Sayyidina Ali is questioned by the Khawarij. His responses, characterized by his profound knowledge and rhetorical skill, successfully persuade the Khawarij to reconsider their stance and ultimately return to the fold of Islam.